A Scoping Review on Shoulder Injuries of Wheelchair Tennis Players: Potential Risk-Factors and Musculoskeletal Adaptations - Mayrhuber, Laura; Rietveld, Thomas; de Vries, Wiebe; van der Woude, Lucas H. V.; de Groot, Sonja; Vegter, Riemer J. K. (Frontiers in Rehabilitation Sciences, 2022)
Wheelchair tennis players are prone to develop shoulder injuries, due to the combination of wheelchair propulsion, overhead activities and daily wheelchair activities. A methodical literature search was conducted to identify articles on shoulder complaints in wheelchair tennis, wheelchair sports and tennis. The aims were to identify 1) type of shoulder complaints; 2) possible risk factors for the development of shoulder injuries; 3) musculoskeletal adaptations in the shoulder joint in wheelchair tennis players. Fifteen papers were included in this review, five on wheelchair tennis, three on wheelchair sports and seven on tennis. Type of shoulder complaints were acromioclavicular pathology, osteoarthritic changes, joint effusion and rotator cuff tears. Possible risk factors for the development of shoulder injuries in wheelchair tennis are overhead movements, repetitive activation of the anterior muscle chain and internal rotators, as well as a higher spinal cord injury level. Muscular imbalance with higher values for the internal rotators, increase in external range of motion, decrease in internal range of motion and reduced total arc of motion were the most common proposed musculoskeletal adaptations due to an unbalanced load. These presented risk factors and musculoskeletal adaptations might help researchers, coaches and wheelchair tennis players to prevent shoulder injuries.